Plow the land and sow: multicultural methodological strategy (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The action research involved proposes interdisciplinary pedagogical practices involving Capoeira Angola and Theater as learning methods for the appreciation of African and Afro-Brazilian History and culture in schools. Drawing on and drawing from authors such as Asante (2009), Rufino (2017) and Thiollent (1986), the methodology aims to combat cosmophobia (Santos, 2019), the expression of the symbolic marginalization of Black culture. Workshops held in public and private institutions promoted the redefinition of ancestral knowledge, expanding the effectiveness of Law nr. 10.639/03 (Brasil, 2003). The approach emphasizes non-domestication (Gonzalez, 1984; Santos, 2023) in involvement in Afrotheatrical scenes.
Keywords: afrocentrism; art education; cosmophobia; capoeira Angola; multicultural curriculum